Effects of starvation, subsequent feeding and photoperiod on flesh quality in farmed cod (Gadus morhua). (27th January 2016) - Bjørnevik, M.; Hansen, H.; Roth, B.; Foss, A.; Vikingstad, E.; Solberg, C.; Imsland, A.K.
Abstract: The study was designed to investigate the effect of four cycles of 5 weeks starvation followed by 10‐week refeeding compared with daily feeding under either natural photoperiod or continuous light (LL) regime on body composition and flesh quality in Atlantic cod in sea cages, northern Norway. The fish were sampled for body composition and flesh quality parameters at the start of the trial, twice at the end of a 10‐week feeding period and twice at the end of a 5‐week starvation period. There was effect of both feeding and light regime on growth, the two starving groups losing weight during starvation and regaining weight during refeeding, and the group under LL being heavier. But, the mean overall growth did not vary between groups. Starvation/refeeding regime resulted in higher slaughter yield, but no overall effect was seen on hepatosomatic index, water content, water holding capacity (WHC), muscle pH, hardness or flesh colour compared with control groups. Continuous light increased gutted weight and slaughter yield, lowered WHC and depressed maturation compared with fish under natural light regime. Increased growth rate resulted in softer fillets and lower muscle pH.